2020
DOI: 10.3389/fped.2019.00515
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Consultation and Prescription in Pediatrics: Contributing Factors and Impact on Clinical Outcomes

Abstract: Objectives: To evaluate phone-based consultation practices and drug prescription profiles in pediatrics and to highlight their possible uses, contributing factors, and effects on clinical outcomes. Background: The ownership and everyday use of cell phones are increasing worldwide. Telehealth is gaining the support of health professionals for the delivery of simple healthcare measures to more complex management decisions. Despite this, in our country, doctors have been advised by concerned authorities to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, the use of telehealth in Lebanon was limited [ 4 ], even though Lebanon has high levels of smartphone (80%) and internet (76%) penetration [ 5 ]. Telehealth activities included small-scale interventions targeted at refugee and underserved populations [ 6 ], as well as the use of telemedicine in well-defined medical tasks [ 7 , 8 ]. However, telehealth services can provide benefits to all the residents of Lebanon in terms of increasing access to healthcare services, raising public health awareness, and providing healthcare training.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, the use of telehealth in Lebanon was limited [ 4 ], even though Lebanon has high levels of smartphone (80%) and internet (76%) penetration [ 5 ]. Telehealth activities included small-scale interventions targeted at refugee and underserved populations [ 6 ], as well as the use of telemedicine in well-defined medical tasks [ 7 , 8 ]. However, telehealth services can provide benefits to all the residents of Lebanon in terms of increasing access to healthcare services, raising public health awareness, and providing healthcare training.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lack of communication channels between primary, secondary, and tertiary healthcare levels, as well as the absence of implementation of electronic prescriptions, can cause inconvenience for both psychiatrists and patients, potentially leading to delays in the patient’s management plan. The implementation of electronic prescriptions should be integrated into a secure electronic system, adhering to specific regulations to mitigate health-related risks and misuse 15. An Irish study investigating the use of electronic prescriptions during the COVID-19 pandemic reported incidents of medication safety issues and near misses among participating general practitioners, primarily attributed to the lack of integration within the existing electronic system and its impact on current workflow practices 16.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of electronic prescriptions should be integrated into a secure electronic system, adhering to specific regulations to mitigate health-related risks and misuse. 15 An Irish study investigating the use of electronic prescriptions during the COVID-19 pandemic reported incidents of medication safety issues and near misses among participating general practitioners, primarily attributed to the lack of integration within the existing electronic system and its impact on current workflow practices. 16 Countries that had implemented electronic prescriptions in their healthcare systems before the pandemic have benefited from improved medication management processes.…”
Section: Discussionmentioning
confidence: 99%
“…Phone consultations are of very frequent use, even more in pediatrics, and they give a high level of satisfaction to the families [35,36]. One expectation of this work was a decrease in phone consultations.…”
Section: Discussionmentioning
confidence: 99%